Student Perception Analysis of AI’s Impact on Arabic Language Learning: A Personality Perspective - Linur, Rahmat; Rusdi, Rusdi; Lubis, Torkis; Rohman, Khabib Syaikhu (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2025)
While numerous studies have highlighted the benefits of AI in language education, the research examining its effectiveness through the lens of personality factors remains limited. Individual personality traits shaping how learners perceive and utilize technology play a critical role in AI-based learning outcomes. This study investigated the relationship between personality traits and AI efficacy in Arabic language learning, framed within the Big Five Personality Traits model (extraversion, openness, conscientiousness, agreeableness, and neuroticism). Through a qualitative survey approach, the data were collected from 27 university students with prior Arabic learning experience (2–4 years) and AI familiarity. Participants included 26 students (96.3%) from pesantren (Islamic boarding schools) and 1 student (3.7%) from a madrasah, all of whom completed questionnaires assessing their perceptions of AI’s role in learning across personality dimensions. Findings reveal that AI enhances learning comfort, adapts to diverse styles, improves grammatical and lexical mastery, and boosts motivation while fostering traits like independence, diligence, and creativity. However, its effectiveness depends on users’ digital literacy, intrinsic motivation, and capacity for reflective learning. The study highlighted the necessity of personalized AI integration in language education, emphasizing adaptive pedagogical support to address individual differences. These insights contributed to the discourse on AI-driven education by bridging personality psychology with technology-enhanced learning, offering practical implications for designing inclusive and effective AI tools in higher education.